Heat radiation resin material, and use of the same

The heat-dissipating resin material addresses the issue of insulation property deterioration at high temperatures by controlling the rate of change in shear adhesion strength, maintaining effective insulation and adhesion in the heat-dissipating resin material.

JP2025059938APending Publication Date: 2025-04-10SUMITOMO BAKELITE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023170355
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing heat-dissipating insulating materials suffer from deterioration in insulation properties over time, especially at high temperatures, and exhibit significant temperature changes.

Method used

A heat-dissipating resin material with a controlled rate of change in shear adhesion strength, within the range of 0-25%, is developed. This material includes an epoxy resin, a thermally conductive filler, and optionally a cyanate resin and hardener, to maintain insulation properties and adhesion strength over time.

Benefits of technology

The heat-dissipating resin material effectively suppresses the reduction in insulation properties due to high-temperature exposure, ensuring excellent adhesion and insulation reliability over time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059938000002
    Figure 2025059938000002
  • Figure 2025059938000001
    Figure 2025059938000001
Patent Text Reader

Abstract

To provide a heat radiation resin material from which a cured product that suppresses lowering of insulation property by a change with the lapse of time under high temperature can be obtained.SOLUTION: A heat radiation resin material has a change rate of shear adhesion strength measured by the following test condition of 0 to 25%, wherein as the test condition, a heat conductive sheet with a dimension of 50 mm×50 mm and thickness of 200 μm, which is composed of the heat radiation resin material, is manufactured by coating the heat radiation resin material, and drying it at 80°C for 30 minutes, the heat conductive sheet is arranged on a copper substrate with thickness of 2.0 mm, a copper foil with thickness of 500 μm is overlapped with the upper surface of the heat conductive sheet, the heat conductive sheet is cured by heating it at 180°C for 45 minutes while applying a pressure of 10 MPa thereto in a thickness direction from above of the copper foil, a laminate in which the copper substrate, an insulation layer with thickness of 200 μm, and the copper foil are laminated in this order is obtained, and a change rate of shear adhesion strength is calculated by the following expression: [(die shear strength before test-die shear strength after heating test) / die shear strength before test]×100.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat dissipating resin material and applications thereof. [Background technology]

[0002] Various developments have been made in the field of heat dissipation and insulation materials. For example, the technology described in Patent Document 1 is known as this type of technology. Patent Document 1 describes a heat dissipation and insulation material constituting electric / electronic devices, etc., which uses a bisphenol A type epoxy resin, a phenolic curing agent, and boron nitride particles as a thermally conductive filler (Table 1 of Patent Document 1).

[0003] Furthermore, Patent Document 2 discloses an epoxy resin composition containing an epoxy resin, a specific phenolic compound in a given amount, and an inorganic filler. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-193504 A [Patent Document 2] JP 2013-237860 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the heat dissipating and insulating materials described in Patent Documents 1 and 2 have room for improvement in that their insulating properties decrease with changes in temperature and the passage of time. [Means for solving the problem]

[0006] The inventors discovered that if the rate of change in shear adhesion strength measured under specific test conditions is within a specified range, the deterioration of insulating properties due to changes over time at high temperatures is suppressed, and thus completed the present invention. That is, the present invention can be shown as follows.

[0007] [1] A heat dissipating resin material whose rate of change in shear adhesion strength measured under the following test conditions is 0 to 25%. (Test conditions) The heat dissipating resin material is applied onto a PET film (dimensions 100 mm x 100 mm) and dried at 80° C. for 30 minutes to produce a heat conductive sheet with a PET film, which is made of the heat dissipating resin material and has dimensions of 50 mm x 50 mm and a thickness of 200 μm. The PET film is peeled off from the obtained heat conductive sheet with a PET film, and the heat conductive sheet is placed on a copper substrate with a thickness of 2.0 mm. A copper foil having a thickness of 500 μm is placed on the upper surface of the thermally conductive sheet, and then the thermally conductive sheet is cured by applying a pressure of 10 MPa from above the copper foil in the thickness direction while heating at 180° C. for 45 minutes to obtain a laminate in which the copper substrate, an insulating layer having a thickness of 200 μm, and the copper foil are laminated in this order. The copper foil is cut into a length of 3 mm x width of 3 mm by cutting, and the copper foil remaining on the surface of the insulating layer is removed by etching to prepare a test sample in which copper chips having a length of 3 mm x width of 3 mm x thickness of 500 μm are laminated. The obtained test sample is stored at 150° C. for 1000 hours. Then, at room temperature (25°C), a bond tester / DAGE-5000 device is used to measure the die shear strength by moving a shear tool horizontally at a speed of 80 m / sec while keeping it 20 μm away from the upper surface of the cured film of the test sample. The rate of change in shear adhesion strength is calculated using the following formula. Formula: [(Die ​​shear strength before test - Die shear strength after heat test) / Die shear strength before test] x 100 [2] The heat dissipating resin material according to [1], comprising an epoxy resin and a thermally conductive filler. [3] The heat dissipating resin material according to [2], further comprising a cyanate resin. [4] The heat dissipating resin material according to claim 2, wherein the thermally conductive filler comprises one or more selected from the group consisting of silica, alumina, boron nitride, aluminum nitride, and silicon carbide. [5] The heat dissipating resin material according to [2], further comprising a curing agent. [6] A laminate comprising a substrate and a layer made of the heat dissipating resin material according to any one of [1] to [5] applied onto the substrate. [7] A heat dissipation insulation sheet laminate according to the laminate described in [6], comprising a heat dissipation insulation sheet formed by curing the layer. [8] A metal substrate; An insulating layer formed by curing the heat dissipation resin material according to any one of [1] to [5]; a metal layer, in that order. Effect of the Invention

[0008] According to the heat dissipation resin material of the present invention, it is possible to provide a cured product in which deterioration of insulating properties due to aging at high temperatures is suppressed. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a cross-sectional view showing a schematic configuration of a metal base substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, the embodiments of the present invention will be described with reference to the drawings. In all drawings, the same components are denoted by the same reference numerals, and the description will be omitted as appropriate. For example, "1 to 10" means "1 or more" to "10 or less" unless otherwise specified.

[0011] The heat dissipating resin material of this embodiment has a rate of change in shear adhesion strength measured under the following test conditions of 0 to 25%, preferably 1 to 23%, and more preferably 3 to 20%. (Test conditions) The heat dissipating resin material is applied onto a PET film (dimensions 100 mm x 100 mm) and dried at 80° C. for 30 minutes to produce a heat conductive sheet with a PET film, which is made of the heat dissipating resin material and has dimensions of 50 mm x 50 mm and a thickness of 200 μm. The PET film is peeled off from the obtained heat conductive sheet with a PET film, and the heat conductive sheet is placed on a copper substrate with a thickness of 2.0 mm. A copper foil having a thickness of 500 μm is placed on the upper surface of the thermally conductive sheet, and then the thermally conductive sheet is cured by applying a pressure of 10 MPa from above the copper foil in the thickness direction while heating at 180° C. for 45 minutes to obtain a laminate in which the copper substrate, an insulating layer having a thickness of 200 μm, and the copper foil are laminated in this order. The copper foil is cut into a length of 3 mm x width of 3 mm by cutting, and the copper foil remaining on the surface of the insulating layer is removed by etching to prepare a test sample in which copper chips having a length of 3 mm x width of 3 mm x thickness of 500 μm are laminated. The obtained test sample is stored at 150° C. for 1000 hours. Then, at room temperature (25°C), a bond tester / DAGE-5000 device is used to measure the die shear strength by moving a shear tool horizontally at a speed of 80 m / sec while keeping it 20 μm away from the upper surface of the cured film of the test sample. The rate of change in shear adhesion strength is calculated using the following formula. Formula: [(Die ​​shear strength before test - Die shear strength after heat test) / Die shear strength before test] x 100

[0012] In this embodiment, by using the "rate of change in shear adhesion strength" measured under the above-mentioned test conditions, the effect on the adhesion strength of the heat dissipating resin material when it is continuously used in a high temperature environment can be evaluated, and the deterioration of insulation due to the temperature conditions of the actual usage environment can be more accurately confirmed. That is, in this embodiment, the "rate of change in shear adhesion strength" measured under the above-mentioned test conditions can be used as an indicator of the adhesion strength of a heat dissipating resin material when used continuously in a high-temperature environment, and by using a heat dissipating resin material whose rate of change is within a predetermined range, changes over time at high temperatures are suppressed, and a product with excellent adhesion and therefore excellent insulation reliability can be provided.

[0013] The heat dissipating resin material in this embodiment contains an epoxy resin and a thermally conductive filler, and preferably further contains a cyanate resin, and more preferably further contains a curing agent. By adjusting the types and amounts of these components added, the above-mentioned numerical range of the rate of change in shear adhesion strength can be satisfied. The components contained in the heat dissipating resin material of this embodiment will be described below.

[0014] [Epoxy resin] As the heat dissipating resin material of this embodiment, a known epoxy resin can be used as long as the effects of the present invention are achieved.

[0015] Examples of such glycidyl ethers include bisphenol A-type, F-type, S-type, and AD-type glycidyl ethers, hydrogenated bisphenol A-type glycidyl ethers, phenol novolac-type glycidyl ethers, cresol novolac-type glycidyl ethers, bisphenol A-type novolac-type glycidyl ethers, naphthalene-type glycidyl ethers, biphenol-type glycidyl ethers, dihydroxypentadiene-type glycidyl ethers, triphenylmethane-type epoxy resins, phenol novolac-type epoxy resins, cresol novolac-type epoxy resins, hydroquinone-type glycidyl ethers, dihydropentadiene-type glycidyl ethers, and biphenyl-type glycidyl ethers. At least one of these can be used.

[0016] The epoxy equivalent of the epoxy resin is, for example, 100 to 300 g / eq, preferably 105 to 290 g / eq, and more preferably 110 to 260 g / eq. By using an epoxy resin having an appropriate epoxy equivalent, it is possible to control the curing property and optimize the physical properties of the cured product.

[0017] In one embodiment, the epoxy resin preferably further contains another epoxy resin that is liquid or semi-solid at room temperature (23° C.). Specifically, it is preferable that a part or all of the epoxy resin is liquid or semi-solid at 23° C. The use of a liquid or semi-solid epoxy resin is preferable in terms of ease of forming a cured product in a desired shape. The heat dissipating resin material of the present embodiment may contain only one type of epoxy resin, or may contain two or more types of epoxy resin.

[0018] The epoxy resin is, for example, 10% by mass to 80% by mass, preferably 15% by mass to 70% by mass, and more preferably 20% by mass to 60% by mass, based on the resin component (100% by mass) of the heat dissipating resin material not including the thermally conductive filler. This ensures sufficient curability, and a cured product with excellent insulation properties can be obtained.

[0019] [Thermal conductive filler] The heat dissipating resin material of this embodiment can use a known heat conductive filler as long as the effects of the present invention are achieved. The thermally conductive filler may include, for example, highly thermally conductive inorganic particles having a thermal conductivity of 20 W / m·K or more. The highly thermally conductive inorganic particles may include, for example, at least one selected from silica, alumina, boron nitride, aluminum nitride, and silicon carbide. These may be used alone or in combination of two or more.

[0020] The boron nitride may include monodisperse particles, agglomerated particles, or a mixture thereof, of scaly boron nitride. The scaly boron nitride may be in the form of granules or chunks, or may be in the form of agglomeration with a binder. By using agglomerated particles of scaly boron nitride, the thermal conductivity can be further increased. The agglomerated particles may be sintered particles or non-sintered particles.

[0021] The content of the thermally conductive filler is 150% by mass to 400% by mass, preferably 200% by mass to 350% by mass, and more preferably 250% by mass to 320% by mass, relative to the resin component (100% by mass) of the heat dissipating resin material. By making it equal to or more than the lower limit, it is possible to improve the thermal conductivity. By making it equal to or less than the upper limit, it is possible to suppress the deterioration of processability.

[0022] [Cyanate resin] The heat dissipating resin material of the present embodiment may further contain a cyanate resin. As the cyanate resin, any known cyanate resin can be used as long as it achieves the effects of the present invention.

[0023] The cyanate resin can be obtained by reacting a cyanide halide compound with a phenol or naphthol. Examples of such cyanate resins include cyanate resins obtained by reacting a phenol novolac type polyhydric phenol with a cyanide halide, a cyanate resin obtained by reacting a cresol novolac type polyhydric phenol with a cyanide halide, and a cyanate resin obtained by reacting a naphthol aralkyl type polyhydric naphthol with a cyanide halide. These may be used alone or in combination of two or more. Among these, from the viewpoint of the effects of the present invention, it is more preferable to contain a phenol novolac type cyanate resin, a dicyclopentadiene type cyanate ester resin, or a naphthol aralkyl type cyanate resin, and it is even more preferable to contain a phenol novolac type cyanate resin.

[0024] The cyanate resin is, for example, 10% by mass to 80% by mass, preferably 15% by mass to 70% by mass, and more preferably 20% by mass to 60% by mass, based on the resin component (100% by mass) of the heat dissipating resin material not including the thermally conductive filler. This ensures more sufficient curing properties, and a cured product with better insulating properties can be obtained.

[0025] [Hardening agent] The heat dissipating resin material of this embodiment may further contain a curing agent. As the curing agent, a known curing agent can be used as long as the effects of the present invention can be achieved, and preferably, a phenol curing agent can be included. As the phenol curing agent, any phenolic curing agent generally used in heat dissipating resin materials can be used as long as the effects of the present invention are achieved.

[0026] Examples of the phenol curing agent include novolac resins obtained by condensing or co-condensing phenols such as phenol novolac resins and cresol novolac resins with formaldehyde or ketones under an acid catalyst, phenol aralkyl resins having a biphenylene skeleton synthesized from the above-mentioned phenols and dimethoxyparaxylene or bis(methoxymethyl)biphenyl, phenol aralkyl resins such as phenol aralkyl resins having a phenylene skeleton, and phenol resins having a trisphenylmethane skeleton. These may be used alone or in combination of two or more.

[0027] The heat dissipation resin material of the present embodiment contains the epoxy resin and the phenolic curing agent, and the ratio d / c of ​​the epoxy equivalent d of the epoxy resin to the hydroxyl equivalent c of the phenolic curing agent can be 1.3 or more, preferably 1.4 or more. By using the epoxy resin and the phenol curing agent so as to fall within the above range, better adhesion can be achieved.

[0028] From the viewpoint of the effects of the present invention, the phenol curing agent can be contained in an amount of preferably 1 to 40 mass %, more preferably 3 to 35 mass %, based on the resin components (100 mass %) of the heat dissipating resin material excluding the thermally conductive filler.

[0029] [Thermosetting resin] The heat dissipating resin material of the present embodiment may contain a thermosetting resin other than the epoxy resin or the cyanate resin. Examples of the thermosetting resin include a thermosetting compound that contains a mesogenic structure (mesogenic skeleton) in the molecule, and a thermosetting compound that does not contain a mesogenic structure in the molecule.

[0030] Examples of the thermosetting resin include maleimide resin, phenol resin, benzoxazine resin, polyimide resin, unsaturated polyester resin, melamine resin, silicone resin, acrylic resin, and phenol derivatives and derivatives thereof, and at least one of these may be included.

[0031] [Cure accelerator] The heat dissipating resin material of this embodiment may contain a curing accelerator (curing catalyst) as necessary. The type and amount of the curing accelerator are not particularly limited, but an appropriate one can be selected from the viewpoints of reaction rate, reaction temperature, storage properties, and the like.

[0032] Examples of the curing accelerator include imidazoles, organic phosphorus compounds, tertiary amines, phenolic compounds, organic acids, etc. These may be used alone or in combination of two or more. Among these, from the viewpoint of improving heat resistance, it is preferable to use nitrogen atom-containing compounds such as imidazoles.

[0033] Examples of the imidazoles include 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenyl-4-methylimidazole, 2,4-diethylimidazole, 2-phenyl-4-methyl-5-hydroxyimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 1-cyanoethyl-2-phenylimidazole, and 1-cyanoethyl-2-phenylimidazolium trimellitate.

[0034] Examples of the tertiary amines include triethylamine, tributylamine, 1,4-diazabicyclo[2.2.2]octane, and 1,8-diazabicyclo(5,4,0)undecene-7.

[0035] Examples of the phenol compound include phenol resin, bisphenol A, nonylphenol, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, and allylphenol. Examples of the organic acid include acetic acid, benzoic acid, salicylic acid, and p-toluenesulfonic acid.

[0036] The content of the curing accelerator may be 0.01% by mass to 10% by mass, 0.02% by mass to 5% by mass, or 0.05% by mass to 1.5% by mass, relative to 100% by mass of the heat dissipating resin material.

[0037] [Other ingredients] The heat dissipating resin material of the present embodiment may contain other components in addition to the above-mentioned components, such as an antioxidant and a leveling agent. As a method for producing the heat dissipating resin material of this embodiment, for example, the following method is available.

[0038] The above components can be dissolved in a solvent, mixed, and stirred to prepare a resin varnish (a varnish-like heat dissipating resin material). This mixing can be performed using a variety of mixers, including ultrasonic dispersion, high-pressure collision dispersion, high-speed rotation dispersion, bead mill, high-speed shear dispersion, and rotation-revolution dispersion.

[0039] The solvent is not particularly limited, but examples thereof include acetone, methyl isobutyl ketone, toluene, ethyl acetate, cyclohexane, heptane, cyclohexanone, tetrahydrofuran, dimethylformamide, dimethylacetamide, dimethylsulfoxide, ethylene glycol, cellosolve-based solvents, carbitol-based solvents, anisole, and N-methylpyrrolidone.

[0040] [Resin sheet (heat dissipation and insulation sheet)] The heat dissipating resin material of this embodiment can provide a resin sheet (heat dissipating insulation sheet) containing the cured product. The specific form of the resin sheet is a heat dissipating insulation sheet laminate including a carrier substrate and a resin layer made of the heat dissipating resin material of this embodiment provided on the carrier substrate.

[0041] The resin sheet can be obtained as a laminate by, for example, applying a varnish-like heat dissipating resin material onto a carrier substrate to obtain a coating film (resin layer) and performing a solvent removal treatment. The solvent content in the resin sheet can be 10 mass% or less based on the entire heat dissipating resin material. For example, the solvent removal treatment can be performed under conditions of 80°C to 200°C and 1 minute to 30 minutes. The obtained resin sheet can be further heated at 150°C to 250°C for 30 minutes to 120 minutes to obtain a heat dissipating insulation sheet laminate having a cured product (heat dissipating insulation sheet). This may be performed under pressure.

[0042] In this embodiment, the carrier substrate may be, for example, a polymer film or a metal foil. Examples of the polymer film include, but are not limited to, polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polycarbonates, release papers such as silicone sheets, and thermoplastic resin sheets having heat resistance such as fluorine-based resins and polyimide resins. Examples of the metal foil include, but are not limited to, copper and / or copper-based alloys, aluminum and / or aluminum-based alloys, iron and / or iron-based alloys, silver and / or silver-based alloys, gold and gold-based alloys, zinc and zinc-based alloys, nickel and nickel-based alloys, and tin and tin-based alloys.

[0043] The resin substrate of the present embodiment includes an insulating layer made of the cured product of the heat dissipation resin material. This resin substrate can be used as a material for a printed circuit board on which electronic components such as LEDs and power modules are mounted.

[0044] <Metal-based substrate> A metal base substrate 100 of this embodiment will be described with reference to FIG. FIG. 1 is a schematic cross-sectional view showing an example of the configuration of a metal base substrate 100. As shown in FIG.

[0045] 1, the metal base board 100 can include a metal substrate 101, an insulating layer 102 provided on the metal substrate 101, and a metal layer 103 provided on the insulating layer 102. The insulating layer 102 can be made of one material selected from the group consisting of a resin layer made of the above-mentioned heat dissipating resin material, a cured product of the heat dissipating resin material, and a laminate. Each of these resin layers and laminates is cured before the circuit processing of the metal layer 103, and is made of the heat dissipating resin material in a stage state.

[0046] The metal layer 103 is provided on the insulating layer 102 and is subjected to circuit processing. Examples of metals constituting the metal layer 103 include one or more selected from copper, copper alloys, aluminum, aluminum alloys, nickel, iron, tin, and the like. Among these, the metal layer 103 is preferably a copper layer or an aluminum layer, and is particularly preferably a copper layer. By using copper or aluminum, the circuit processing property of the metal layer 103 can be improved. The metal layer 103 may be a metal foil available in a plate shape, or a metal foil available in a roll shape.

[0047] The lower limit of the thickness of the metal layer 103 is, for example, 0.01 mm or more, and preferably 0.035 mm or more, so long as it is applicable to applications requiring a high current. The upper limit of the thickness of the metal layer 103 is, for example, 10.0 mm or less, and preferably 5 mm or less. If the thickness is less than this value, the circuit processability can be improved, and the substrate as a whole can be made thinner.

[0048] The metal substrate 101 has a role of dissipating heat accumulated in the metal base substrate 100. The metal substrate 101 is not particularly limited as long as it is a heat dissipating metal substrate, but may be, for example, a copper substrate, a copper alloy substrate, an aluminum substrate, or an aluminum alloy substrate, with a copper substrate or an aluminum substrate being preferred, and a copper substrate being more preferred. By using a copper substrate or an aluminum substrate, the heat dissipation properties of the metal substrate 101 can be improved. The thickness of the metal substrate 101 can be appropriately set as long as it does not impair the object of the present invention.

[0049] The upper limit of the thickness of the metal substrate 101 is, for example, 20.0 mm or less, and preferably 5.0 mm or less. If the thickness is less than this value, the workability of the metal base substrate 100 in the contour processing, cutting processing, and the like can be improved.

[0050] The lower limit of the thickness of the metal substrate 101 is, for example, 0.01 mm or more, and preferably 0.3 mm or more. By using a metal substrate 101 having a thickness equal to or greater than this value, the heat dissipation properties of the metal base substrate 100 as a whole can be improved.

[0051] In this embodiment, the metal base substrate 100 can be used for various substrate applications, but because of its excellent thermal conductivity and heat resistance, it can be used as a printed circuit board that uses an LED or a power module.

[0052] The metal base substrate 100 may have a metal layer 103 that is circuitized by etching or the like into a pattern. In this metal base substrate 100, a solder resist (not shown) may be formed on the outermost layer, and connection electrodes may be exposed so that electronic components can be mounted thereon by exposure and development.

[0053] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted as long as they do not impair the effects of the present invention. EXAMPLES

[0054] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these.

[0055] (Examples 1 to 7, Comparative Example 1) <1. Preparation of heat dissipating resin material> According to the formulation shown in Table 1, a thermosetting resin, a curing agent, and a curing catalyst were added to a solvent, methyl ethyl ketone, and the mixture was stirred to obtain a mixed solution. Next, boron nitride particles, an inorganic filler, were added to the mixed solution and premixed, and then kneaded with a three-roll mill to obtain a varnish-like heat-dissipating resin material (thermosetting resin composition) in which the boron nitride particles were uniformly dispersed. Next, the obtained heat-dissipating resin material was aged at 30°C for 15 hours.

[0056] The ingredients shown in Table 1 are as follows: (thermosetting resin) Epoxy resin 1: Cresol novolac epoxy resin (N-690, Dainippon Ink Co., Ltd.) Epoxy resin 2: Epoxy resin with a dicyclopentadiene skeleton (XD-1000, manufactured by Nippon Kayaku Co., Ltd.) Epoxy resin 3: Epoxy resin with a naphthalene skeleton (HP-4700, manufactured by DIC Corporation) Epoxy resin 4: Epoxy resin with a biphenyl skeleton (YX-4000, manufactured by Mitsubishi Chemical Corporation) Epoxy resin 5: Bisphenol F type epoxy resin (830S, manufactured by Dainippon Ink Co., Ltd.) Cyanate resin 1: Phenol novolac type cyanate resin (PT-30, manufactured by Lonza Japan Co., Ltd.) Phenoxy resin 1: Bisphenol A phenoxy resin (YP-55, Nippon Steel Chemical)

[0057] (hardening agent) Phenol-based hardener 1: Trisphenylmethane type phenol novolac resin (MEH-7500, manufactured by Meiwa Kasei Co., Ltd.)

[0058] (curing catalyst) Curing catalyst 1: 2-phenyl-4,5-dihydroxymethylimidazole (2PHZ-PW, manufactured by Shikoku Kasei Co., Ltd.)

[0059] (Inorganic filler) Inorganic filler 1: Boron nitride particles (average particle size 20-40 μm), HP-40 (manufactured by JFE Mineral Co., Ltd.) Inorganic filler 2: Boron nitride particles (average particle size 20-40 μm), UHP-G1H (Showa Denko) Inorganic filler 3: Boron nitride particles (average particle size 5-10 μm), S03 (Tokuyama Corporation)

[0060] <2. Physical property measurement> -Shear adhesion strength measurement The varnish-like heat dissipating resin material was applied onto a PET film (dimensions: 100 mm x 100 mm) and dried at 80° C. for 30 minutes to produce a heat conductive sheet with a PET film having dimensions of 50 mm x 50 mm and a thickness of 200 μm, which was made of the heat dissipating resin material. The PET film was peeled off from the obtained heat conductive sheet with a PET film, and the heat conductive sheet was placed on a copper substrate having a thickness of 2.0 mm. A copper foil having a thickness of 500 μm was placed on the upper surface of the thermally conductive sheet, and then the thermally conductive sheet was cured by heating at 180° C. for 45 minutes while applying a pressure of 10 MPa in the thickness direction from above the copper foil, thereby obtaining a laminate in which the copper substrate, an insulating layer having a thickness of 200 μm, and the copper foil were laminated in this order. The copper foil was cut into a length of 3 mm x width of 3 mm by cutting, and the copper foil remaining on the surface of the insulating layer was removed by etching to prepare a test sample in which a copper chip having a length of 3 mm x width of 3 mm x thickness of 500 μm was laminated. The shear adhesion strength of the prepared test sample was measured under the following test conditions.

[0061] (Test conditions: high temperature storage) The prepared test sample was stored at 150°C for 1000 hours. Then, at room temperature (25°C), a bond tester / DAGE-5000 device was used to measure the die shear strength by moving a shear tool at a speed of 80 m / sec in the horizontal direction while keeping it 20 μm away from the upper surface of the cured film of the test sample. The rate of change in shear adhesion strength was calculated using the following formula. Formula: [(Die ​​shear strength before test - Die shear strength after heat test) / Die shear strength before test] x 100

[0062] Insulation reliability evaluation An AC voltage of 4.0 kV was applied to the cured thermal conductive sheet after high temperature storage in the measurement of shear adhesion strength for 1 minute to check whether or not it broke. (Evaluation Criteria) 〇: Insulation maintained for 1 minute or more at an applied AC voltage of 4.0 kV ×: Dielectric breakdown in less than 1 minute at an applied AC voltage of 4.0 kV

[0063] -Volume resistivity measurement The volume resistivity of the thermally conductive sheet cured product (before high-temperature storage) obtained in the shear adhesion strength measurement was measured as follows: According to JIS K6911, the volume resistivity of the cured product was measured (25° C.) 1 minute after applying a voltage of 1000 V using an ULTRA HIGH RESISTANCE METER R8340A (manufactured by ADC Corporation). The main electrode was made using conductive paste. The main electrode was made in a circular shape with a diameter of 50 mm. The guard electrode was made around the main electrode with an inner diameter of 70 mm and an outer diameter of 80 mm. The counter electrode was made with a diameter of 83 mm. The evaluation criteria were as follows: ◎: Volume resistance value 1×10 10 Ω cm or more 〇: Volume resistance value 1×10 9 Ω cm or more, 1×10 10 Less than Ω cm × : Volume resistance value 1×10 9 Less than Ω cm

[0064] -Thermal conductivity measurement The heat dissipation resin material obtained in each example was heated and cured at 175°C for 30 minutes to obtain a sheet cured product (10 mm x 10 mm x 1.0 mm thick). The thermal conductivity in the thickness direction of the cured sheet was then calculated using the following formula from the thermal diffusion coefficient (α) measured by the laser flash method (half-time method), the specific heat (Cp) measured by the DSC method, and the density (ρ) measured in accordance with JIS-K-6911. The unit of thermal conductivity is W / m K. Thermal conductivity [W / m K]=α[mm 2 / s]×Cp[J / kg K]×ρ[g / cm 3 ]

[0065] [Table 1] [Explanation of symbols]

[0066] 100 Metal base board 101 Metal Substrate 102 Insulating layer 103 Metal layer

Claims

1. A heat dissipating resin material having a change rate of shear adhesion strength of 0 to 25% measured under the following test conditions: (Test conditions) The heat dissipating resin material is applied onto a PET film (dimensions 100 mm x 100 mm) and dried at 80° C. for 30 minutes to produce a heat conductive sheet with a PET film having dimensions of 50 mm x 50 mm and a thickness of 200 μm, which is made of the heat dissipating resin material. The PET film is peeled off from the obtained heat conductive sheet with a PET film, and the heat conductive sheet is placed on a copper substrate having a thickness of 2.0 mm. A 500 μm thick copper foil is placed on the upper surface of the thermally conductive sheet, and then the thermally conductive sheet is cured by heating at 180° C. for 45 minutes while applying a pressure of 10 MPa in the thickness direction from above the copper foil, thereby obtaining a laminate in which the copper substrate, a 200 μm thick insulating layer, and the copper foil are laminated in that order. The copper foil is cut into a size of 3 mm in length and 3 mm in width by cutting, and the copper foil remaining on the surface of the insulating layer is removed by etching to prepare a test sample having a copper chip of 3 mm in length, 3 mm in width, and 500 μm in thickness. The obtained test sample is stored at 150° C. for 1000 hours. Then, at room temperature (25° C.), a bond tester / DAGE-5000 device is used to measure the die shear strength by moving a shear tool horizontally at a speed of 80 m / sec with the shear tool spaced 20 μm from the upper surface of the cured film of the test sample. The rate of change in shear adhesion strength is calculated using the following formula. Formula: [(die shear strength before test−die shear strength after heat test) / die shear strength before test]×100

2. The heat dissipation resin material according to claim 1 , comprising an epoxy resin and a thermally conductive filler.

3. The heat dissipating resin material according to claim 2 , further comprising a cyanate resin.

4. The heat dissipating resin material according to claim 2 , wherein the thermally conductive filler comprises one or more selected from the group consisting of silica, alumina, boron nitride, aluminum nitride, and silicon carbide.

5. The heat dissipation resin material according to claim 2 , further comprising a curing agent.

6. A substrate; A layer made of the heat dissipating resin material according to any one of claims 1 to 5, applied onto the substrate.

7. 7. The laminate of claim 6, further comprising a heat dissipation insulation sheet formed by curing said layer.

8. A metal substrate; An insulating layer formed by curing the heat dissipation resin material according to any one of claims 1 to 5; a metal layer, in that order.

Citation Information

Patent Citations

  • Epoxy resin composition and cured product

    JP2013237860A

  • Boron nitride particle, resin composition and heat-conductive sheet

    JP2015193504A